Repair of spontaneous perineal laceration at delivery, a cultural taboo: a case report (2006)
Although genital trauma is a recognized maternal complication of vaginal birth, the presence of skilled birth attendants at delivery and judicious use of episiotomy has been shown to reduce this risk to the barest minimum. Prompt repair of these traumas averts the resultant complications that may arise. A case of a booked 18-year-old nulliparous Guinea-Conakry woman with a second-degree perineal tear who declined repair due to a cultural reason is presented. The need for supervised delivery as well as immediate and long-term health implications of her decision is discussed.